THE EFFECT OF JOB MOTIVATION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE SATISFACTION - Angellika, Viny; Masman, Ronnie Resdianto (International Journal of Application on Economics and Business, 2023)
This study aimed to determine the effect of work motivation on employee job satisfaction and the effect of organizational commitment on employee job satisfaction at PT. XYZ in Central Jakarta. The sampling method illustrated in this research uses convenience sampling with 100 employees as respondents, 5 of whom were respondents in the initial survey of the study and 95 employees were respondents in the study. The Smart PLS3 analytical kit was used in this study. The results showed an influence of work motivation on the job satisfaction of PT. XYZ employees in Central Jakarta, and there was an influence of organizational commitment on the job satisfaction of PT. XYZ employees in Central Jakarta.